Older adults’ reasons for applying to a nursing home – a document analysis - Lisa Spang; Kajsa Lidström-Holmqvist; Marie Holmefur; Cecilia Pettersson (Scandinavian Journal of Occupational Therapy)
Background Ageing in place is the social norm in Sweden, yet older adults apply for a nursing home on a daily basis which suggests that ageing in place needs further study as it is not suitable for everyone. Aim: to study descriptions of older adults’ reasons for applying to a nursing home in documents of granted nursing home decisions.Materials and methods One hundred and sixty decisions were analyzed through document analysis with a deductive content analysis using the Canadian Model of Occupational Performance-Engagement (CMOP-E) as a framework.Results Reasons for applying were represented in the three factors of the CMOP-E. In personal factors, reason for applying was e.g. connected to severe anxiety. In environmental factors, family culture had an influence in the application. In occupational factors, the ability to perform self-care and mobility greatly affected decisions to apply to nursing homes.Conclusion Descriptions of the older adults’ activities in daily life were limited. If OTs were further involved in nursing home applications, adults ageing in place could be better supported and a move to a nursing home may be prevented. Significance: this study contributes to the understanding of why older adults chose to apply to a nursing home.